(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the peculiarities of translating the business letters. We consider in detail the stereotype cliches as a component of semantic structures that may be grouped on thematic basis. Special attention is paid to the abbreviations and shortened words, with their creation and functioning promoting linguistic economy and making the content more understandable and informative for a specific circle of specialists.